Curcumin and cinnamon mitigates lead acetate-induced oxidative damage in the spleen of rats - Emam, Mahmoud Abdelghaffar; Farouk, Sameh Mohamed; Aljazzar, Ahmed; Abdelhameed, Abeer A.; Eldeeb, Abeer A.; Gad, Fatma Abdel-monem (Frontiers in Pharmacology, 2023)
Lead toxicity is a common occupational and environmental health hazard that exerts many toxic effects to animals and humans including immunotoxicity. Curcumin (CUR) and cinnamon (CIN) are common medicinal herbs with immunostimulatory and antioxidant properties. Therefore, this study investigated the protective effect of CUR and CIN against lead acetate (LA)-induced splenotoxicity in rats via hemato-biochemical, immunological, oxidative stress markers, CYP-2E1 expression, histological and immunohistological evaluations. Four groups of six rats/each were used including control group received corn oil as a vehicle, LA group received (100 mg/kg), CUR+LA group received CUR (400 mg/kg) plus LA, and CIN+LA group received CIN (200 mg/kg) plus LA orally for 1 month. LA-exposure induced macrocytic hypochromic anemia, leukocytosis, neutrophilia, monocytosis and lymphopenia. Additionally, significant elevations in serum iron, ferritin levels and transferrin saturation% with significant decline of total and unsaturated iron binding capacities (TIBC and UIBC), transferrin, immunoglobulin G and M levels were recorded. Besides, LA significantly up-regulated splenic CYP-2E1 expression, that evident by significant depletion of reduced glutathione (GSH) activity, and elevation of malondihyde (MDA), nitric oxide (NO), and protein carbonyl (PC) concentrations in spleen. Histologically, hyperplasia of lymphoid follicles, hemosiderin deposition, and disturbance of CD3 and CD68 immuno-expressions were evident in spleen from LA group. However, CUR and CIN administration restored the hemato-biochemical, immunological, oxidative stress parameters as well as histological and immunohistological pictures toward the normalcy. In conclusion, CUR and CIN can partially ameliorate LA-induced oxidative damage in spleen, possibly through their antioxidant, immunomodulatory and gene-regulating activities.